The 500-year Cultural & Economic Trajectory of Tobacco: A Circle Complete - Christopher A. Jones; Amanda Wassel; William Mierse; E. Scott Sills (Journal of Health Economics and Outcomes Research)
Who smokes, and why do they do it? What factors discourage and otherwise reward or incentivize smoking? Tobacco use has been accompanied by controversy from the moment of its entry into European culture, and conflicting opinions regarding its potentially adverse influence on health have coexisted for hundreds of years. Its use in all forms represents the world’s single greatest cause of preventable disease and death. Tobacco was introduced to Europe by Christopher Columbus, who in October 1492 discovered the crop in Cuba. While the next four centuries would see tobacco as the most highly traded economic commodity, by 1900, the now familiar cigarette remained obscure and accounted for only 2% of total tobacco sales. Global tobacco consumption rose sharply after 1914 and became especially prevalent following World War II, particularly among men. Indeed, overall tobacco sales increased by more than 60% by the mid-20th century, and cigarettes were a critical driver of this growth. Cigarettes dominated the tobacco market by 1950, by then accounting for more than 80% of all tobacco purchases. In the absence of clinical and scientific evidence against tobacco, moral and religious arguments dominated opposition voices against tobacco consumption in the 1800s. However, by the mid-20th century, advancements in medical research supported enhanced government and voluntary actions against tobacco advertising and also raised awareness of the dangers associated with passive tobacco smoke exposure. Solid epidemiological work connecting tobacco use with “the shortening of life span” began to appear in the medical literature in the 1950s, linking smoking with lung cancer and related conditions. In subsequent years, these developments led to significant curtailment of tobacco use. This monograph explores aspects of the intersection of tobacco with themes of behavioral incentives, religion, culture, literature, economics, and government over the past five centuries.